2019
DOI: 10.1080/13102818.2018.1534556
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a MADS-box gene in cucumber (Cucumis sativus L.) that affects flowering time and leaf morphology in transgenic Arabidopsis

Abstract: View related articles View Crossmark data Citing articles: 2 View citing articles Isolation and characterization of a MADS-box gene in cucumber (Cucumis sativus L.) that affects flowering time and leaf morphology in transgenic Arabidopsis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…RT-PCR was performed to examine the expression of CsMADS01 in different developmental stages of MF and FF using the reaction procedure previously described (Zhou et al, 2019a). The primer sequences are listed in Table S1.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…RT-PCR was performed to examine the expression of CsMADS01 in different developmental stages of MF and FF using the reaction procedure previously described (Zhou et al, 2019a). The primer sequences are listed in Table S1.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…The closest references were retrieved from NCBI GenBank and aligned with CLUSTAL W with all parameters set at their default values. Phylogenetic trees were then generated by a neighbour-joining algorithm [20] and Maximum Composite Likelihood model of base substitution as implemented in MEGA7.0.14 [21]. The trees were validated using bootstrap analysis performed with 1000 replicates.…”
Section: Identification Of Dmp-degrading Bacteriamentioning
confidence: 99%
“…Moreover, the MIKC-type proteins own an extremely conserved MADS domain and three moderately conserved domains (I, K and C) [ 6 ]. The various members of the MADS-box gene family have been known to participate predominantly in developmental processes, such as plant vegetative reproduction [ 7 , 8 ], flower organ formation [ 9 , 10 , 11 ], male and female gametophyte development [ 12 ] and fruit development [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the triple mutants SEP1/2/3 in Arabidopsis caused all flower organs to turn into sepals. Additionally, the SEP gene could shorten the vegetative growth period and promote the early flowering of plants [ 11 , 18 , 20 , 21 , 22 ]. Besides the genes in the ABCDE model, other MADS-box genes are also responsible for sepal development.…”
Section: Introductionmentioning
confidence: 99%